Multifunctional Properties of Quercitrin-Coated Porous Ti-6Al-4V Implants for Orthopaedic Applications Assessed In Vitro - Llopis-Grimalt, Maria Antonia (J Clin Med, 2020)
(1) One strategy to improve the outcome of orthopedic implants is to use porous implants with the addition of a coating with an antibacterial biomolecule. In this study, we aimed to produce and test the biocompatibility, the osteopromotive (both under normal conditions and under a bacterial challenge with lipopolysaccharide (LPS)) and antibacterial activities of a porous Ti-6Al-4V implant coated with the flavonoid quercitrin in vitro. (2) Porous Ti-6Al-4V implants were produced by 3D printing and further functionalized with quercitrin by wet chemistry. Implants were characterized in terms of porosity and mechanical testing, and the coating with quercitrin by fluorescence staining. Implant biocompatibility and bioactivity was tested using MC3T3-E1 preosteoblasts by analyzing cytotoxicity, cell adhesion, osteocalcin production, and alkaline phosphatase (ALP) activity under control and under bacterial challenging conditions using lipopolysaccharide (LPS). Finally, the antibacterial properties of the implants were studied using Staphylococcus epidermidis by measuring bacterial viability and adhesion. (3) Porous implants showed pore size of about 500 µm and a porosity of 52%. The coating was homogeneous over all the 3D surface and did not alter the mechanical properties of the Young modulus. Quercitrin-coated implants showed higher biocompatibility, cell adhesion, and osteocalcin production compared with control implants. Moreover, higher ALP activity was observed for the quercitrin group under both normal and bacterial challenging conditions. Finally, S. epidermidis live/dead ratio and adhesion after 4 h of incubation was lower on quercitrin implants compared with the control. (4) Quercitrin-functionalized porous Ti-6Al-4V implants present a great potential as an orthopedic porous implant that decreases bacterial adhesion and viability while promoting bone cell growth and differentiation.